Antimicrobial Activity of Crude Protein Extracts of Seriphidium kurramense - Ahmad, Kafeel; Afridi, Waqar Ahmed; Ali, Amjad; Aziz, Aamir (Asian Journal of Chemistry, 2016)
Current study was aimed at investigating antibacterial and antifungal activities of crude protein extracts of Seriphidium kurramense. Agar well diffusion assays were performed to screen crude protein extracts against methicillin resistant Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, Bacillus subtillus, Staphylococcus aureus and Salmonella typhi. Antifungal assay was carried out against Aspergillus niger, Aspergillus flavus, Alternaria solani, Rhizoctonia solani, Fusarium solani and Pleurotus florida. Different dilutions of crude protein extracts were used. The protein extracts showed antimicrobial activity against bacterial and fungal strains. However, pure extracts were more potent than a 1:1 dilution of protein extracts.